(untitled) (Bangladesh Journal of Medical Science, 2022)
Aim:In this study, it was aimed to determine nursing students perceptions of caring behaviors and the factors affecting them. Methods:In the study, no sample was selected, 205 students who accepted to participate voluntarily were included in the study. Data were collected by using the personal information form and Caring Assessment Questionnaire. Data were analyzed by SPSS. Results:The mean total score of the Caring Assessment Questionnaire was found 270.65±50.55. The Cronbach alpha coefficient of the scale was found0.96. When the total mean score of the scale was compared with the personal characteristics of the students, no statistically significant difference was found between gender, working experience, hospitalization experience, caregiving experience status and negative experiences during the care process. However, it was found that there was a statistically significant difference between the grades, care-taking experience and opinions that care is the primary duty of the nurse. Also a statistically significant difference was found between all subscales and the students who think that nursing care is the primary duty. Conclusion:As a result, students perceptions of care behaviors scored above the average. High care perceptions of students will lead to positive progress in their professional life and provide them to be qualified health professional. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 639-644